Introduction to Special Issue on New Studies in EROI (Energy Return on Investment) - Charles A.S. Hall (Sustainability, 2011)
Energy Return on Investment (EROI) refers to how much energy is returned from one unit of energy invested in an energy-producing activity. It is a critical parameter for understanding and ranking different fuels. There were a number of studies on EROI three decades ago but relatively little work since. Now there is a whole new interest in EROI as fuels get increasingly expensive and as we attempt to weigh alternative energies against traditional ones. This special volume brings together a whole series of high quality new studies on EROI, as well as many papers that struggle with the meaning of changing EROI and its impact on our economy. One overall conclusion is that the quality of fuels is at least as important in our assessment as is the quantity. I argue that many of the contemporary changes in our economy are related directly to changing EROI as our premium fuels are increasingly depleted.